Debugging Microservices with Pandas, PySpark using Actuators and Logs at Runtime - Shukla, Sameer (International Journal of Computer Sciences and Engineering, 2022)
Microservices architecture is distributed in nature and the expectation is the services in the architecture must be highly available and responsive. Services in the architecture can scale from 1 to 100s and the distributed architecture is complex, and the chances of failure are higher when services communicate to each other. The main advantage of microservice architecture is we can easily mix technologies depending upon the nature of service, if the service is CPU or IO bound then we can develop the service based on the language or framework of our choice, similarly if we have hundreds of services in our architecture than we can build a proper debugging system for our microservices using any platform / frameworks two such libraries are Pandas or PySpark. This paper focuses on creating our own debugging tool in the Microservices architecture using python-based libraries PySpark and Pandas and the concept of Actuators.